The concept of "functionalities" in a macroeconomic modelling framework - Insights for Austria. EconTrans working paper #3 - Mark Sommer; Angela Köppl; Stefan P. Schleicher; Gabriel Bachner; Jakob Mayer; Laura Fischer; Karl W. Steininger (Austrian Institute of Economic Research (WIFO), 2021)
In this paper we take up the challenge to integrate new aspects into macroeconomic modelling and to consider economic activities from an outcome-oriented perspective, so called functionalities. The basic idea is, that functionalities lie behind the demand for commodities and services and therefore are the actual reason for economic activities. Functionalities describe (basic) human needs, such as housing, nutrition, or mobility, and are determinants of human well-being. A crucial aspect of functionalities is the interaction between stocks and flows. The paper presents the operationalisation of functionalities within the framework of an Input-Output (IO) model. Three extensions of the IOT are performed: Firstly, an appropriate allocation of energy supply, transformation and demand to sectors is made. This allows linking the monetary structure with physical units of the total energy and useful energy balances. Secondly, greenhouse gas emissions and other material consumption were additionally allocated to sectoral production. Thirdly, groups of goods of private and public consumption as well as exports were allocated to specific functionalities.
Keywords: 330